Usefulness of inflammatory biomarkers in discriminating between bacterial and aseptic meningitis in hospitalized children from a population with low vaccination coverage - Gowin, Ewelina (Arch Med Sci, 2016)
INTRODUCTION: Neisseria meningitidis and Streptococcus pneumoniae are the most frequent pathogens responsible for meningitis beyond the neonatal period. Aseptic meningitis is a disabling condition, but bacterial meningitis if left untreated is 100% fatal. The aim of the study was to analyze the usefulness of biochemical and hematological parameters in distinguishing between bacterial and non-bacterial meningitis in children with meningitis from a population with low rates of vaccination against S. pneumoniae and N. meningitidis. MATERIAL AND METHODS: This study is a retrospective chart review of children hospitalized with meningitis. In patients with aseptic and bacterial meningitis the following parameters were compared: C-reactive protein, D-dimers, fibrinogen, glucose level, and leukocyte level, and in cerebrospinal fluid, protein, glucose, and leukocyte concentrations were analyzed. Number of points in the Bacterial Meningitis Score (BMS) was calculated. The predictive value of each parameter to distinguish between bacterial and aseptic meningitis was evaluated. RESULTS: In total, 129 patients were included in the study: 65 diagnosed with bacterial meningitis and 64 with aseptic meningitis. Bacterial and aseptic meningitis were statistically significantly different based on each analyzed parameter (p < 0.000001). Among children with aseptic meningitis 42 (66%) scored 0 points in the BMS, while all the children with bacterial meningitis had at least one point. CONCLUSIONS: In children with meningitis inflammatory biomarkers differ statistically significantly depending on the etiology – bacterial or aseptic. Serum concentration of C-reactive protein higher than 80 mg/dl is a useful marker of bacterial etiology of meningitis. A high Bacterial Meningitis Score is indicative for bacterial meningitis.